Driving Employee Digital Performance: Exploring The Mediating Role Of Employee Dynamic Capability In The Context Of Hi-Hrmp And Organizational Learning At Pt Astra Daihatsu Motor In Sunter & Karawang - Reffi Nurhardiyanti; Tiarapuspa (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2024)
This study investigates the relationship of High Involvement Human Resources Management Practice (HI-HRMP), Organizational Learning, Employee Dynamic Capability and Employee Digital Performance. The primary objective is aiming to explore how Employee Dynamic Capability mediates the effect of HI-HRMP and Organizational Learning on Employee Digital Performance. The research focuses on employees of PT Astra Daihatsu Motor in Sunter and Karawang, involving a sample of 185 respondents selected using purposive sampling from company’s workforce in both location. The research employs a quantitative approach, utilizing a questionnaire to collect cross-sectional data. Data analysis includes descriptive statistics to summarize the sample characteristics and mean, the Sobel test to examine the mediating effect of employee dynamic capability, and Structural Equation Modeling (SEM) to analyze the relationships between variables. The finding shows that HI-HRMP has a direct positive and significant effect on employee digital performance but does not influence on employee dynamic capability. Thus, dynamic capability fails to mediate the relationship between HI-HRMP and employee digital performance. Meanwhile, organizational learning significantly influence employee digital performance, both directly or indirect and through employee dynamic capability as a partially mediating variable.